Learning Progression: How should we teach about disease to determine students’ level of understanding? - Roni Ardiansyah; H. Harlita; Murni Ramli (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Strengthening Learning Progression (LP) for students' reasoning abilities is important, especially learning about diseases in Indonesia. This study aimed to map the learning progression of disease in Indonesia, compare and analyze its similarities and differences with the LP designed by National Reseaarch Council (NRC). This qualitative research to map LP, using the analysis documen method by comparing the content analysis of Basic Competencies of Curriculum 13 with benchmark analysis from the NRC 2007 on Science and Biology textbooks published in 2016, 2017, and 2018 at the elementary, junior high, and high school levels published by the Ministry of Education and Culture of the Republic of Indonesia. The findings are the LP on disease in the curriculum and life science textbooks in Indonesia has not met the benchmarks, especially in three categories, namely; pathogens, the immune system, and infection spanning learning from K-2 (elementary) to K-12 (high school). Therefore, it is necessary to categorize LP topics in diseases based on conceptual abilities from the simplest to the most complex.